TIME HAS CHANGED: A PHENOMENOLOGICAL STUDY OF FARMERS' LIVES AMID INDUSTRIAL EXPANSION - Muhammad Anggit Hendrawan; Siwi Gayatri; Yanuar Luqman (RADJA PUBLIKA, 2025)
The development of the Kendal Industrial Estate (KIK), as part of Indonesia's national industrialization agenda, has resulted in large-scale land conversion in Wonorejo Village, Kendal. This study aims to deeply examine the transformation of fish farmers’ lives following the conversion of agrarian space into industrial zones. Employing a qualitative approach through an Interpretative Phenomenological Analysis (IPA) design, this research explores the subjective experiences of five directly affected farmers. Data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that the relocation of fish ponds triggered income decline, disruption of local agribusiness supply chains, and a crisis in farmers’ social identity. Although some successfully transitioned to new occupations, adaptive inequality emerged due to differing levels of social and economic capital. Farmers who failed to adapt experienced structural marginalization and a loss of social status within the village community. These findings reflect a process of agrarian dispossession, where farmers lost access to the means of production without fully integrating into the modern industrial labor system. Moreover, the disappearance of ponds damaged the local food production ecosystem and eroded community-based values such as mutual cooperation. While KIK has delivered macroeconomic benefits, including increased investment and employment opportunities, the development remains poorly integrated with local economic systems in an equitable and sustainable manner. Based on these results, it is recommended that land conversion policies actively involve affected communities, ensure fair compensation, and safeguard the socio-ecological sustainability of rural livelihoods. This study emphasizes the need for development approaches that pursue not only economic growth but also justice and resilience for agrarian societies at the local level.